PROBLEMATIKA ANAK MENJALANKAN IBADAH DALAM KELUARGA MULTI AGAMA DI KOTA PALANGKA RAYA - Hamdanah Hamdanah (AL-TAHRIR, 2014)
Problems of humans vary considerably. One major problem concerns religion. Under a normal condition, one can observe religious rites properly. Problems arise, however, when one, especially children, lives in a family whose members practice different religions. This can be seen, for example, in many families in Palangkaraya, Central Kalimantan. The decision to follow a particular religion and practice it in a multi religious family is challenging. There is a problem between the conscience to practice the religion in accordance to one’s own faith and the pressure to follow parents or foster parents who practice different religious. This article examines not only how adolescents choose their own religion but also how they practice religious rites in a multi religious families. Using qualitative-fenomenology approach, the data consitsed of ten families and were collected trough partipative observation and depth interview techniques. Findings show that adolescents have serious problems not only as to how they decide their own religion but also how they should observe their religious rituals. They felt confused, doubt, and event affraid of doing religious rites differently in such families. Findings also show that there are correlations between parents’ defferent religion and their low-motivation in religious activities and understanding religion.